Intramode wave packet with spectrum in the vicinity of zero frequency of the TM-mode group velocity of thin left-handed material; Молодежь и современные информационные технологии; Т. 1 - Rahim A. A. R. (Микропроцессорные системы, компьютерные сети и телекоммуникации, 2016)
Заглавие с титульного экрана